2011
DOI: 10.1128/jvi.00682-11
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis C Virus Infection Is Blocked by HMGB1 Released from Virus-Infected Cells

Abstract: High-mobility group box 1 (HMGB1), an abundant nuclear protein that triggers host immune responses, is an endogenous danger signal involved in the pathogenesis of various infectious agents. However, its role in hepatitis C virus (HCV) infection is not known. Here, we show that HMGB1 protein is translocated from the nucleus to cytoplasm and subsequently is released into the extracellular milieu by HCV infection. Secreted HMGB1 triggers antiviral responses and blocks HCV infection, a mechanism that may limit HCV… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
53
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 60 publications
(53 citation statements)
references
References 43 publications
0
53
0
Order By: Relevance
“…HMGB1 is translocated from the nucleus to the cytoplasm and subsequently is released into the extracellular milieu by HCV or HBV infection (61)(62)(63). Extracellular HMGB1 during HCV infection can trigger the interferon antiviral response through a TLR4-dependent pathway (61,63). HMGB1 serum levels are significantly higher in patients with chronic HBV than in normal healthy people and are closely related to the stage of inflammation and fibrosis in the liver ( Figure 4A) (64).…”
Section: Hmgb1 and Viral Hepatitismentioning
confidence: 99%
See 1 more Smart Citation
“…HMGB1 is translocated from the nucleus to the cytoplasm and subsequently is released into the extracellular milieu by HCV or HBV infection (61)(62)(63). Extracellular HMGB1 during HCV infection can trigger the interferon antiviral response through a TLR4-dependent pathway (61,63). HMGB1 serum levels are significantly higher in patients with chronic HBV than in normal healthy people and are closely related to the stage of inflammation and fibrosis in the liver ( Figure 4A) (64).…”
Section: Hmgb1 and Viral Hepatitismentioning
confidence: 99%
“…Although multiple signaling networks are responsible for coordinating the inflammatory and immune response during virus hepatitis, HMGB1 is critical in initiating and mediating these effects. HMGB1 is translocated from the nucleus to the cytoplasm and subsequently is released into the extracellular milieu by HCV or HBV infection (61)(62)(63). Extracellular HMGB1 during HCV infection can trigger the interferon antiviral response through a TLR4-dependent pathway (61,63).…”
Section: Hmgb1 and Viral Hepatitismentioning
confidence: 99%
“…2C). One recent study demonstrated that HMGB1 released from virus-infected cells could block HCV infection (35). Therefore, we speculated that the ectopic expression of HMGB1 may increase the amount of extracellular HMGB1, which partially neutralized the effect of intracellular HMGB1 on HCV propagation.…”
Section: Hmgb1 Promotes Hcv Replication Without Affecting Viral Transmentioning
confidence: 99%
“…Both RNA virus, including hepatitis C virus, dengue virus, and human immunodeficiency virus (HIV) (34)(35)(36)(37), and DNA virus, including herpes simplex virus 2 (48) infections result in the secretion of HMGB1. HMGB1 protein secreted in response to viral infections may contribute to the pathogenesis of these infections.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation